Analisis Peluang Penyertaan Modal Pemerintah Daerah Kota XYZ pada PT Bank Jawa Barat dan Banten (Bank BJB) (Jurnal Manajemen dan Organisasi, 2016)
Economic growth and public welfare are the reason of regional autonomy regulation policy (UU No 22 year 1999). The policy allows regional economic resources managed by regional government to achieve its goal. One of the regional government strategies is investment strategy, which in this case investing in banking industry. The purposes of the study are 1) to identify the investment regulation on regional government 2) to identify the Bank BJB business and investment environment 3) to identify the comparison of investment feasibility on Bank BJB versus other banks 4) to identify the position of Stock Share A series owned by XYZ at Bank BJB. The data collection methods are using structured interview, in depth interview, field survey and literature study. The analysis tools are using institutional analysis, SWOT analysis and financial analysis. Institutional analysis showed XYZ regional government investment management is limited to regulation as follow 1) long term capital (stock share) investment limited only at BUMD (e.g. Bank BJB) 2) short term investment e.g. saving and deposit is limited only at healthy and feasible bank, and government bond which has small risk exposure. The financial analysis also showed the increasing performance of BJB Earning per Share (EPS) and Return on Equity (ROE) from 2006 until 2010. The SWOT analysis support other analysis that BJB Bank position in financial industry is suitable for long term and short term investment for XYZ regional government. Base on explanation above, the conclusions are the autonomy regulation limited XYZ regional government to invest as shareholders in A series (stock share) or B series (stock share) at BJB Bank only, and for short term investment is limited only at healthy and feasible bank, and government bond which has small risk exposure.